Meningkatkan Motivasi dan Pemahaman Konsep Perbandingan Fungsi Trigonometri melalui Model Pembelajaran Jigsaw di SMA Negeri 8 Kota Jambi - Fitri Haryani (Universitas Jambi, 2012)
Classroom action research by applying the Jigsaw learning model was conducted in learning of Mathematics in class X of SMAN 8 Jambi in the second semester of 2012. The results show that the Jigsaw learning model enhanced students’ motivation on the concept of comparison of trigonometric functions from 40% to 66%. The Jigsaw learning model also enhances the degree of student learning completeness on the comparative trigonometric functions concept by 31%. In addition the Jigsaw model also boosted students’ competence in terms of comparison of trigonometric functions from 45 to 70 after the class action research.